Gadolinium(III) and europium(III) L-glutamates: Synthesis and characterization - Barja, Beatriz Carmen (2006)
Two lanthanide(III) complexes with L-glutamate ligands [{Ln2(L-Glu)2(H2O)8}.4(ClO4).2.5H2O]n (Ln = Gd (1), Eu (2)) have been prepared and characterized by single-crystal X-ray diffraction. The compounds are isomorphous with infinite cationic 2D layers stacked together by secondary bonds. The building blocks are slightly different non-centrosymmetric dinuclear units placed in alternating layers, the resulting structures thus containing four non-equivalent Ln metal sites. The dinuclear units contain a fourfold bridge, two in the eta1:eta1:mi2 and two in the eta2:eta1:mi2 modes, from two alfa- and two gamma-carboxylates of four different L-Glu residues, respectively.